2021
DOI: 10.1182/blood-2021-153258
|View full text |Cite
|
Sign up to set email alerts
|

A Bicistronic Vector Expressing CD16 and a Membrane Bound IL-15 Construct in iPSC Derived NK Cells Increased Cytotoxicity and Persistence

Abstract: Current cell and gene therapy medicines for oncology have reshaped how cancer is treated. Specifically, chimeric antigen receptor (CAR)-T cells have demonstrated that cell therapy can achieve durable remissions in hematologic malignancies. However, CAR-T cell therapies have limited efficacy in solid tumors and are often associated with severe toxicity, highlighting the need for novel cell therapies that are safer and more efficacious. With their intrinsic killing capacity of tumor cells and few, if any, treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Therefore, the LDH release assay is frequently employed for assessing the cytotoxicity of NK-92 cells. 49 Results confirmed that the NK-92-CDL+NIR group showed a significant LDH release, as more NK-92 cells came into contact with tumor cells and exerted strong immune function (Figure 4J). The high antitumor and antimigration effect could be attributed to the NIR light-activated cell assembly approach.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Therefore, the LDH release assay is frequently employed for assessing the cytotoxicity of NK-92 cells. 49 Results confirmed that the NK-92-CDL+NIR group showed a significant LDH release, as more NK-92 cells came into contact with tumor cells and exerted strong immune function (Figure 4J). The high antitumor and antimigration effect could be attributed to the NIR light-activated cell assembly approach.…”
Section: Resultssupporting
confidence: 56%
“…The presence of LDH in the extracellular milieu is indicative of cell membrane damage. Therefore, the LDH release assay is frequently employed for assessing the cytotoxicity of NK-92 cells . Results confirmed that the NK-92-CDL+NIR group showed a significant LDH release, as more NK-92 cells came into contact with tumor cells and exerted strong immune function (Figure J).…”
Section: Resultsmentioning
confidence: 61%